2014
DOI: 10.5433/1679-0359.2014v35n1p531
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade interna de ovos submetidos a diferentes tipos de revestimento e armazenados por 35 dias a 25ºC

Abstract: ResumoEste trabalho teve por objetivo avaliar a qualidade interna de ovos submetidos a dois tipos de revestimento: gelatina a 3%, óleo mineral comercial e sem revestimento (controle). Foram utilizados 180 ovos brancos, com peso médio de 62 g, provenientes de galinhas poedeiras da linhagem Shaver White. Estes ovos foram armazenados a uma temperatura de 25° C em uma BOD, durante 35 dias e foram analisados a cada sete dias. Foram avaliados a porcentagem de gema, porcentagem de albúmen, porcentagem de casca, porce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 5 publications
3
13
0
10
Order By: Relevance
“…Through the results of specific gravity (Table 3), we observed an average of 1.070 g cm -³ for all marketed eggs, with no difference between the treatments. Even fresh eggs had specific gravity values similar to those found by Pissinati et al (2014), who obtained values of specific gravity of 1.076 g cm -³ for eggs stored for up to 14 days, whereas grocery store eggs presented similar values (1.068 g cm -³) to the eggs stored for 21 days. The albumen height, Haugh Unit (UH) and albumen index of eggs collected in farms presented the best results, when compared to these data obtained from supermarkets and grocery store eggs.…”
Section: Resultssupporting
confidence: 81%
“…Through the results of specific gravity (Table 3), we observed an average of 1.070 g cm -³ for all marketed eggs, with no difference between the treatments. Even fresh eggs had specific gravity values similar to those found by Pissinati et al (2014), who obtained values of specific gravity of 1.076 g cm -³ for eggs stored for up to 14 days, whereas grocery store eggs presented similar values (1.068 g cm -³) to the eggs stored for 21 days. The albumen height, Haugh Unit (UH) and albumen index of eggs collected in farms presented the best results, when compared to these data obtained from supermarkets and grocery store eggs.…”
Section: Resultssupporting
confidence: 81%
“…The eggshells coated with 2% of gelatin (T5) showed WL not different significantly to the heat treatments and the control group, which shows that the solution used (2%) did not leave a suitable barrier able to prevent egg water losses to the external environment. Pissinati et al (2014) observed improvements in weight maintenance when using 3% of gelatin.…”
Section: Discussionmentioning
confidence: 90%
“…A perda de peso do ovo está relacionada com a temperatura, circulação de ar e também com a umidade relativa do local em que o ovo é submetido durante o armazenamento. Em temperaturas mais elevadas e umidade relativa do ar menor, essa perda tende a aumentar mais do que em ovos que são mantidos em temperaturas menores, ou submetidos à refrigeração (PISSINATI et al, 2014). A temperatura ideal para o armazenamento de ovos encontra-se entre 10 a 15°C, e indicando uma melhor condição de conservação para a qualidade e conseguindo assim uma diminuição da perda de qualidade do ovo (LANA, 2000).…”
Section: Resultsunclassified
“…Estes valores são resultantes da correlação que ocorre entre a altura do albúmen e o peso dos ovos da unidade Haugh. Esse processo de perda de qualidade é completamente dependente do período e da temperatura de armazenamento e apresenta maior velocidade durante os primeiros dias após a postura, estudos relatam que ovos mantidos em menores temperaturas apresentam valores mais elevados de UH que os ovos que são mantidos em temperatura ambiente (PIRES et al, 2015), isso se deve pela liquefação do albúmen, processo que se acelera em temperatura ambiente, reduzindo a altura do albúmen, uma das variáveis utilizadas para mensuração da UH (LANA et al, 2017).…”
Section: Sistemas De Criaçãounclassified